Aluminum removal method for removing aluminum from composite resin film

JP2025002436APending Publication Date: 2025-01-09ENVIRONMENT SYST CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023102612
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-22
Publication Date
2025-01-09

AI Technical Summary

Benefits of technology

【0013】 前記第2過程を実行する時点における前記水酸化ナトリウム水溶液の温度を20℃よりも低い温度とすることができる。この場合前記第2過程を実行した後(つまり、複合樹脂フィルムを水酸化ナトリウム水溶液に水没させた後)、前記第3過程を実行する前に、20℃より低い温度から、前記第3過程における前記所定の温度まで前記水酸化ナトリウム水溶液の温度を上昇させる予熱過程を実行するようにしてもよい。 水酸化ナトリウム水溶液の温度が高い、例えば、30℃よりも高いときに、そのようなある程度高温な水酸化ナトリウム水溶液に複合樹脂フィルムを水没させると、水酸化ナトリウム水溶液とアルミニウム層を構成するアルミニウムとが過剰に反応し、上述の(1)の式で特定される化学反応が勢いよく生じて水素が大量に発生することがある。水素の大量発生は危険を伴うことがあるし、もちろん適切な措置を講じることによりそのような危険を避けることは可能であるが、その措置を講じるために手間とコストが生じることになる。対して、20℃よりも温度が低い水酸化ナトリウム水溶液に複合樹脂フィルムを水没させ、その後水酸化ナトリウム水溶液の温度を例えば30℃まで上昇させた場合には、そのような水素の大量発生が生じないことを、本願発明者は実験により見出した。 したがって、第2過程実施時、つまり複合樹脂フィルムが投入される時点の水酸化ナトリウム水溶液の温度を上述したように20℃よりも低い温度とし、その後第3過程を実施するまでに、水酸化ナトリウム水溶液の温度を、第3過程を実施する際の水酸化ナトリウム水溶液の温度にまで上昇させることとすれば、ある程度高温の水酸化ナトリウム水溶液を用いることによるある程度高速のアルミニウムの溶解速度を維持しつつ、水素の大量発生を避けることが可能となる。 前記予熱過程の実行時間は、10分から30分のなるべく短い時間、可能であれば10分から20分程度の範囲の時間とするのが好ましい。予熱過程を実行する時間があまりにも短いと、水素の大量発生の抑制の効果が十分に得られないことも想定される。しかしながら、予熱過程があまりにも長いと、本願のアルミニウム除去方法の実施に要する時間が長くなりすぎるおそれがある。その観点からすれば予熱過程の時間は、水素の大量発生の抑制の効果が得られる範囲でなるべく短くすべきである。予熱過程の実行時間を上述の範囲とすれば、水素の大量発生の抑制の効果を得るには十分であり、アルミニウム除去方法の実施に必要な時間が過剰に延びることもない。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025002436000001
    Figure 2025002436000001
  • Figure 2025002436000002
    Figure 2025002436000002
  • Figure 2025002436000003
    Figure 2025002436000003
Patent Text Reader

Abstract

To provide a practical technology for taking out a resin by removing aluminum from a composite resin film.SOLUTION: Both surfaces of a composite resin film are covered with a resin layer, and the composite resin film includes therein an aluminum layer composed of aluminum. A large number of holes are made in the composite resin film. Then, the composite resin film is immersed in a sodium hydroxide aqueous solution. A temperature of the sodium hydroxide aqueous solution is controlled from 25°C to 50°C, and a concentration of sodium hydroxide is controlled from 9.72% to 23.9%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a technique for removing aluminum from a composite resin film having an aluminum layer. [Background technology]

[0002] Composite resin films having an aluminum layer (hereinafter, sometimes simply referred to as "composite resin films") are widely used. For example, composite resin films having an aluminum layer are widely used for packaging snack foods and other foods, and medicines. The composite resin film has an aluminum layer. The aluminum layer may be a foil, or may be formed by vapor-depositing aluminum onto an adjacent resin layer. A resin layer is provided on each side of the aluminum layer. The resin layers provided on both sides of the aluminum layer may each be a single layer, but are usually made of multiple layers made of different resins. By assigning different functions to the aluminum layer and both resin layers (or the layers of multiple types of resin that make up each of the resin layers), the composite resin film is able to exhibit the desired functions. The composite resin film is prepared in a roll shape and is printed appropriately according to the product to be packaged. The prepared composite resin film is cut to an appropriate width and length, and then processed into packaging products, such as packages such as bags.

[0003] As mentioned above, the composite resin film is prepared with the appropriate printing for the item to be packaged. However, if there is a change in the product to be packaged, the printing on the composite resin film will also need to be changed. Even if there is no change in the product to be packaged, there may be cases where the advertising strategy needs to be changed, which requires a change in the package, and therefore it will be necessary to change the printing on the composite resin film. Since it is practically impossible to correct printing that has already been applied to the composite resin film, when such a situation occurs, the entire roll of composite resin film is discarded. And since the above-mentioned circumstances that make it necessary to discard the composite resin film occur with a certain frequency, the amount of composite resin film to be discarded is enormous.

[0004] By the way, awareness of the SDGs has been increasing in recent years. Under such circumstances, it is of course not desirable to simply discard a large amount of composite resin film. Since the composite resin film contains resin, if it were possible to extract only the resin by removing the aluminum from the aluminum layer and leaving only the resin layer, it would be possible to recover a large amount of resin from the composite resin film that would otherwise be discarded. The recovered resin can be reused in some form, which of course also leads to a reduction in the environmental burden. From this viewpoint, a technique has been proposed for removing aluminum from a composite resin film and recovering the resin. It is common knowledge that aluminum dissolves in an alkaline aqueous solution, and a technique has been proposed in which a composite resin film is immersed in an alkaline aqueous solution to dissolve only the aluminum in the composite resin film, thereby recovering the resin in the composite resin film. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 4574543 [Patent Document 2] Patent No. 5014488 [Patent Document 3] Patent No. 6777263 Summary of the Invention [Problem to be solved by the invention]

[0006] However, previous technologies had problems such as the time required to dissolve the aluminum in the composite resin film being too long, and the reaction when dissolving the aluminum in the composite resin film being too violent, requiring measures to be taken to ensure safety, and although the technology may be viable in principle, it is difficult to put into practical use.

[0007] An object of the present invention is to provide a practical technique for removing aluminum from a composite resin film and extracting the resin. [Means for solving the problem]

[0008] In order to solve the above problems, the present inventors propose the following invention. The present invention is an aluminum removal method (hereinafter, sometimes simply referred to as "aluminum removal method") for removing aluminum from a composite resin film that includes an aluminum layer made of aluminum and two resin layers that cover both sides of the aluminum layer. The composite resin film from which aluminum is to be removed by this aluminum removal method is the same as the composite resin film described in the Background Art section. This aluminum removal method includes a first step of providing grooves or holes that reach the aluminum layer from the surface of at least one of the two resin layers; a second step of immersing the composite resin film that has undergone the first step in an aqueous sodium hydroxide solution having a concentration of 9.72% (by weight, the same applies below) to 23.9%; a third step of, after the second step, continuing to submerge the composite resin film in the aqueous sodium hydroxide solution while maintaining the temperature of the aqueous sodium hydroxide solution at a predetermined temperature of 25°C to 50°C until substantially all of the aluminum that constitutes the aluminum layer is dissolved; and a fourth step of removing the composite resin film from which the aluminum layer has been removed, from the aqueous sodium hydroxide solution after the third step is completed. This aluminum removal method includes a first step of providing grooves or holes that reach the aluminum layer from the surface of at least one of the two resin layers of the composite resin film. In other words, at the stage where the first step is completed, the aluminum layer present inside the composite resin film is exposed from at least one of the two resin layers through the grooves or holes. The holes may or may not penetrate the composite resin film. It is preferable that there are a large number of grooves and holes. It is preferable that there are a large number of grooves and holes evenly distributed throughout the entire composite resin film. However, consideration should be given to the grooves and holes so that they do not cause a decrease in the strength of the composite resin film to the extent that the composite resin film breaks. In this aluminum removal method, the composite resin film after the first step is immersed in an aqueous sodium hydroxide solution in the second step. The sodium hydroxide concentration of the aqueous sodium hydroxide solution is 9.72% to 23.9%. In the third step of this aluminum removal method, the composite resin film is submerged in the aqueous sodium hydroxide solution, and the temperature of the aqueous sodium hydroxide solution is maintained at a predetermined temperature of 25°C to 50°C while the composite resin film is submerged in the aqueous sodium hydroxide solution until the aluminum constituting the aluminum layer is substantially all dissolved. In the present application, when 98% or more of the aluminum constituting the aluminum layer is dissolved, it is said that the aluminum is "substantially all" dissolved. When the third step is being performed, it is preferable to stir the aqueous sodium hydroxide solution, either batchwise or continuously, in order to promote contact between the aluminum in the aluminum layer and the aqueous sodium hydroxide solution. Since the aluminum layer in the composite resin film is almost entirely dissolved, the aluminum removal method then includes a fourth step in which the composite resin film from which the aluminum layer has been removed is taken out of the sodium hydroxide aqueous solution. In this aluminum removal method, the first step is performed to expose an aluminum layer that would normally be present inside the composite resin film (to be precise, the aluminum layer may be exposed to the outside at the edge of the composite resin film without the need to provide the above-mentioned grooves or holes) from at least one of the two resin layers through the grooves or holes, which makes it easier for the aqueous sodium hydroxide solution to come into contact with the aluminum layer in the second step and subsequent steps. Conventional methods for removing aluminum from composite resin films did not include a process corresponding to the first step in the aluminum removal method of the present application. Therefore, in conventional methods, the alkaline aqueous solution first comes into contact with the aluminum layer exposed only at the edges of the composite resin film, and then proceeds toward the aluminum layer at the center of the composite resin film while dissolving the aluminum layer. In comparison, the aluminum removal method of the present application, which performs the first step to expose the aluminum layer through grooves or holes at various positions in the two resin layers and submerges the composite resin film in a sodium hydroxide aqueous solution, makes it possible to significantly shorten the time required to dissolve the aluminum. Specifically, the time required for dissolving almost all of the aluminum in the aluminum layer using the aluminum removal method of the present invention is generally within 8 hours, and in some cases within 6 hours. The ability to carry out the aluminum removal method for removing aluminum from a composite resin film within a time period of about 8 hours or about 6 hours is of great significance in terms of the practical application of the aluminum removal method, for example, in terms of balancing with factory operation hours.

[0009] The reason why the concentration of the aqueous sodium hydroxide solution and the temperature are set within the above-mentioned ranges is as follows. When an aqueous solution of sodium hydroxide comes into contact with aluminum, the reactions represented by the following chemical equations (1) and (2) occur. Al + NaOH + 3 H2O → Na[Al(OH)4] + 3 / 2 H2……(1) Al + 3NaOH → Al(OH)3……(2) All of these reactions dissolve aluminum, but the Al(OH)3 produced in the reaction shown in chemical equation (2) precipitates in an aqueous sodium hydroxide solution. In an aqueous solution of sodium hydroxide, the following reaction, shown in chemical equation (3), also occurs: Al(OH)3+ NaOH → Na[Al(OH)4]……(3) In reaction (3), the Al(OH)3 produced in reaction (2) dissolves again in the sodium hydroxide solution. As this reaction occurs, the amount of precipitate in the sodium hydroxide solution decreases. However, as the amount of Na[Al(OH)4] on the right side of the chemical equation (3) increases due to reaction (1), reaction (3) reaches chemical equilibrium, and the reaction from the left side to the right side of (3) no longer occurs. In other words, as the dissolution of aluminum progresses due to reaction (1), the above-mentioned chemical equilibrium is reached, making it more difficult for reaction (3) to occur, and therefore the amount of precipitated Al(OH)3 in the sodium hydroxide solution gradually increases. In making the present invention, the applicant carried out experiments in which the concentration and temperature of the aqueous sodium hydroxide solution were changed under various conditions. From the experiments and the results, the applicant discovered the following. First, the reaction (1) above occurs more actively the higher the concentration of sodium hydroxide in the aqueous sodium hydroxide solution, and, as is the case with many chemical reactions, occurs more actively at higher temperatures. Therefore, in order to efficiently cause the above reaction (1) and efficiently or quickly dissolve aluminum, the concentration of sodium hydroxide and the temperature should be high. This is quite common sense. However, the applicant has found through experiments that when the concentration of sodium hydroxide in the aqueous sodium hydroxide solution is higher than a certain concentration, or when the temperature of the aqueous sodium hydroxide solution is higher than a certain temperature, the reaction (2) described above occurs actively, or the reaction (3) described above does not occur sufficiently, or both occur simultaneously. As a result, a large amount of Al(OH)3 precipitates in the aqueous sodium hydroxide solution. The increase in the amount of Al(OH)3 precipitates is a very serious problem in the aluminum removal method of the present application. This is because, in the aluminum removal method of the present application, the sodium hydroxide aqueous solution comes into contact with the aluminum in the aluminum layer through the grooves and holes provided in the resin layer in the first process, thereby promoting the dissolution of the aluminum, and if the above-mentioned precipitates adhere to the grooves and holes, the contact of the sodium hydroxide aqueous solution with the aluminum is hindered. Considering the strength of the composite resin film, it is difficult to increase the width and size of the above-mentioned grooves and holes, so if the precipitates adhere to them, the contact of the sodium hydroxide aqueous solution with the aluminum is easily hindered. In consideration of such points, the inventors of the present application have found that it is not advisable to focus only on the above-mentioned reaction (1) and unnecessarily increase the concentration of sodium hydroxide in the aqueous sodium hydroxide solution or to unnecessarily increase the temperature of the aqueous sodium hydroxide solution. Then, from various experiments and consideration of the results, it was found that by setting the sodium hydroxide concentration of the sodium hydroxide aqueous solution in which the composite resin film was submerged to 9.72% to 23.9%, and maintaining the temperature of the sodium hydroxide aqueous solution in which the composite resin film was submerged at 25°C to 50°C, the aluminum that makes up the aluminum layer of the composite resin film would essentially all dissolve within approximately eight hours. The lower limit of the sodium hydroxide concentration, 9.72%, and the lower limit of the temperature, 25°C, are the minimum concentration and temperature required to promote the above-mentioned reaction (1), while the upper limit of the sodium hydroxide concentration, 23.9%, and the upper limit of the temperature, 50°C, are the concentration and temperature required to avoid excessive reaction (2) or to sufficiently promote reaction (3).

[0010] Although not limited thereto, the composite resin film before the first step is performed may be a long piece and rolled up. In fact, as explained in the Background Art section, a long piece and rolled up is a very common form of a composite resin film before use. When the composite resin film is of such a type, in the first step, while the rolled composite resin film is being continuously unwound from its leading end and wound up from its leading end to be rolled up again, a process may be performed on the composite resin film running between two rolls to provide a groove or hole that reaches the aluminum layer from the surface on at least one side of the two resin layers of the composite resin film. In this way, it is possible to provide grooves or holes over the entire length of the long composite resin film, which allows the aluminum in the aluminum layer to come into contact with the aqueous sodium hydroxide solution over the entire length of the composite resin film, thereby shortening the time required to carry out the aluminum removal method.

[0011] As described above, the concentration of sodium hydroxide in the aqueous sodium hydroxide solution used in the aluminum removal method of the present application is 9.72% to 23.9%, and this concentration is desirably 13.0% to 22.0% in the second and third steps. By doing so, the time required to dissolve substantially all of the aluminum in the aluminum layer can be almost certainly kept to 8 hours or less. In the second and third steps, a 14.1% to 20.5% aqueous sodium hydroxide solution is used, and the predetermined temperature in the third step can be 30° C. or higher. By doing so, the time required to dissolve substantially all of the aluminum in the aluminum layer can be almost certainly kept to six hours or less. In the second and third steps, a 13.0% to 21.5% aqueous sodium hydroxide solution is used, and the predetermined temperature in the third step can be 35° C. or higher. This also ensures that the time required to dissolve substantially all of the aluminum in the aluminum layer is within six hours.

[0012] In the aluminum removal method of the present invention, it is preferable to control the sodium hydroxide concentration and temperature of the aqueous sodium hydroxide solution in the third step as follows. In the third step, the predetermined temperature of the aqueous sodium hydroxide solution is constant, and the sodium hydroxide concentration C [%] and temperature T [K] of the aqueous sodium hydroxide solution can satisfy the following formula. k 290 (C)+[k 313 (C)-k 290 (C)]×(T-290) / 23≧0.00815 min -1 however, k 290 (C)=0.00157+0.00554×Exp[-0.0141×(C-18.4) 2 ] k 313 (C)=(0.302+2.02×Exp[-0.00881×(C-15.2) 2 ])×k 290 (C) By adjusting the sodium hydroxide concentration and temperature of the aqueous sodium hydroxide solution so that C and T satisfy these conditions, the time required to dissolve almost all of the aluminum in the aluminum layer in the composite resin film can be reduced to about 8 hours or less. In addition, in the third step, the predetermined temperature of the aqueous sodium hydroxide solution can be constant, and the sodium hydroxide concentration C [%] and temperature T [K] of the aqueous sodium hydroxide solution can satisfy the following formula. k 290 (C)+[k 313 (C)-k 290 (C)]×(T-290) / 23≧0.0100 min -1 however, k 290(C)=0.00157+0.00554×Exp[-0.0141×(C-18.4) 2 ] k 313 (C)=(0.302+2.02×Exp[-0.00881×(C-15.2) 2 ])×k 290 (C) By adjusting the sodium hydroxide concentration and temperature of the aqueous sodium hydroxide solution so that C and T satisfy these conditions, the time required to dissolve almost all of the aluminum in the aluminum layer in the composite resin film can be reduced to about 6 hours or less.

[0013] The temperature of the aqueous sodium hydroxide solution at the time of performing the second step may be lower than 20° C. In this case, after performing the second step (i.e., after the composite resin film is submerged in the aqueous sodium hydroxide solution), a preheating step may be performed to increase the temperature of the aqueous sodium hydroxide solution from a temperature lower than 20° C. to the predetermined temperature in the third step before performing the third step. When the temperature of the aqueous sodium hydroxide solution is high, for example, higher than 30°C, if a composite resin film is immersed in such a relatively high temperature aqueous sodium hydroxide solution, the aqueous sodium hydroxide solution and the aluminum constituting the aluminum layer may react excessively, and the chemical reaction specified by the above formula (1) may occur vigorously, resulting in the generation of a large amount of hydrogen. The generation of a large amount of hydrogen may be dangerous, and of course it is possible to avoid such danger by taking appropriate measures, but taking such measures will require time and cost. In contrast, the present inventors have found through experiments that if a composite resin film is immersed in an aqueous sodium hydroxide solution that is lower than 20°C and then the temperature of the aqueous sodium hydroxide solution is increased to, for example, 30°C, such a large amount of hydrogen is not generated. Therefore, if the temperature of the aqueous sodium hydroxide solution when the second step is carried out, i.e., at the time when the composite resin film is introduced, is set to a temperature lower than 20°C as described above, and then, before the third step is carried out, the temperature of the aqueous sodium hydroxide solution is raised to the temperature of the aqueous sodium hydroxide solution when the third step is carried out, it is possible to avoid the generation of large amounts of hydrogen while maintaining a relatively high aluminum dissolution rate achieved by using an aqueous sodium hydroxide solution at a relatively high temperature. The execution time of the preheating process is preferably as short as possible, between 10 and 30 minutes, and preferably between 10 and 20 minutes. If the execution time of the preheating process is too short, it is expected that the effect of suppressing the large amount of hydrogen generation may not be sufficiently obtained. However, if the preheating process is too long, the time required to implement the aluminum removal method of the present application may become too long. From this viewpoint, the time of the preheating process should be as short as possible within the range in which the effect of suppressing the large amount of hydrogen generation can be obtained. If the execution time of the preheating process is within the above-mentioned range, it is sufficient to obtain the effect of suppressing the large amount of hydrogen generation, and the time required to implement the aluminum removal method is not excessively extended. [Brief description of the drawings]

[0014] [Figure 1] 1 is a cross-sectional view of an example of a composite resin film from which aluminum is removed by the aluminum removal method of the present invention. [Diagram 2] FIG. 4 is a side view conceptually showing a method for drilling holes in a composite resin film. [Diagram 3] FIG. 2 is a plan view of a composite resin film having holes therein. [Figure 4] FIG. 4 is a front view showing a method of submerging a roll of composite resin film in an aqueous sodium hydroxide solution. [Diagram 5] FIG. 3 is a cross-sectional view of the composite resin film used in the test. [Figure 6] Table 1 shows the test results. [Figure 7] Table 2 shows the change in the amount of aluminum over time when the concentration of sodium hydroxide aqueous solution is 20% and the reaction temperature is 17°C. [Figure 8] Graph 1 shows the change in the natural logarithm of the reaction rate over time for each concentration of sodium hydroxide solution when the temperature of the sodium hydroxide solution is 17°C. [Figure 9] Graph 2 shows the change in the natural logarithm of the reaction rate over time for each concentration of sodium hydroxide solution when the temperature of the sodium hydroxide solution is 40°C. [Figure 10] Table 3 shows the reaction rate constants for each concentration of sodium hydroxide solution when the temperature of the sodium hydroxide solution is 17°C (290K) and 40°C (313K). [Figure 11] Graph 3 shows the magnitude of the reaction rate constant versus the concentration of sodium hydroxide aqueous solution when the temperature of the sodium hydroxide aqueous solution is 17°C and 40°C, obtained by plotting the reaction rate constants in Table 3 and then performing curve fitting. [Figure 12] Graph 4 shows reaction curves when the temperatures of the aqueous sodium hydroxide solution are 17°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, and 50°C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, an embodiment of the present invention will be described with reference to the drawings.

[0016] The following describes a method for removing the aluminum that constitutes the aluminum layer 11 from the composite resin film. An example of a composite resin film 1 from which aluminum has been removed by the aluminum removal method is shown in Figure 1. Figure 1 is a cross-sectional view. The composite resin film 1 itself may be an existing one, or in fact is usually an existing one. The composite resin film 1 comprises an aluminum layer 11 and resin layers 12, 13 covering both sides of the aluminum layer 11. The composite resin film 1 of this embodiment is used to manufacture a bag (not shown) for packaging a specified product. When the composite resin film 1 is made into a bag, the resin layer 12 is located on the inner side of the bag, and the resin layer 13 is located on the outer side. The aluminum layer 11 is made of aluminum. The aluminum layer may be an aluminum foil or may be formed by vapor deposition on one of the adjacent resin layers 12, 13. Both resin layer 12 and resin layer 13 are made of resin. Resin layer 12 and resin layer 13 may be made of the same resin or different resins. In the example shown in Fig. 1(A), resin layer 12 and resin layer 13 are both single layers made of one type of resin, but resin layer 12 and resin layer 13 may both be multiple layers made of different resins. In Fig. 1(B), resin layer 13 has a three-layer structure of a first outer resin layer 13A, a second outer resin layer 13B, and a third outer resin layer 13C. In the example shown in Fig. 1(A), typically, resin layer 12 is polypropylene (PP) or polyethylene (PE), etc., and resin layer 13 is polyethylene terephthalate (PET) or nylon (NY), etc. To explain a typical example, the thicknesses of aluminum layer 11, resin layer 12, and resin layer 13 in the composite resin film 1 shown in Fig. 1(A) are 6 µm to 8 µm, 40 µm to 80 µm, and 20 µm to 30 µm, respectively. In the example shown in Fig. 1(B), typically, the resin layer 12 is made of PE, the first outer resin layer 13A is made of NY, the second outer resin layer 13B is made of biaxially oriented polypropylene (OP), and the third outer resin layer 13C is made of PET. To explain a typical example, the thicknesses of the aluminum layer 11, the resin layer 12, the first outer resin layer 13A, the second outer resin layer 13B, and the third outer resin layer 13C in the composite resin film 1 shown in Fig. 1(B) are 9 μm, 40 μm to 120 μm, 12 μm, 24 μm, and 15 μm, respectively. The resins constituting each of the resin layers 12 and 13 (the first outer resin layer 13A, the second outer resin layer 13B, and the third outer resin layer 13C) have different properties and play different roles. The roles played by each resin are not relevant to the present application, so detailed explanations will be omitted.

[0017] Although not limited to this, in this embodiment, the composite resin film 1 is an elongated object and is in a roll shape. The following description will be given assuming that the composite resin film 1 was originally used to manufacture the above-mentioned bag, but for some reason is no longer usable for making bags.

[0018] When carrying out the aluminum removal method on the composite resin film 1, the following first to third steps are carried out. In addition, although not necessarily required, in this embodiment, a preheating step is carried out between the second and third steps. The first to third steps and the preheating step will be described below.

[0019] The first step is to provide grooves or holes that reach the aluminum layer 11 from the surface of at least one of the two resin layers 12 and 13 of the composite resin film. In the case of providing grooves, at least one of the surfaces of the resin layers 12 and 13 is scraped with, for example, comb-shaped teeth to provide grooves that reach at least the aluminum layer 11. There are no particular limitations on the width, length, direction, and number per unit area of ​​the grooves, but they should be such that the contact of the aluminum layer 11 with the sodium hydroxide aqueous solution, which will also be described later, is sufficiently promoted in the preheating process and the third process, which will be described later. The grooves may penetrate the aluminum layer 11. Also, if the grooves are provided from the resin layer 12, they may penetrate the aluminum layer 11 and the resin layer 13, and if the grooves are provided from the resin layer 13, they may penetrate the aluminum layer 11 and the resin layer 12. In these cases, the grooves become elongated holes and cannot be distinguished from holes, which will be described later. As described above, there are no particular limitations on the width, length, direction, and number per unit area of ​​the grooves, but providing the grooves may result in a decrease in strength of the composite resin film 1. For example, it should be noted that it is necessary to provide grooves in the composite resin film 1 so that the composite resin film 1 does not break when tension described below is applied to the composite resin film 1, or so that the composite resin film 1 does not break when the aluminum that constitutes the aluminum layer 11 melts when the preheating process and the third process described below are performed. When holes are provided, holes reaching at least the aluminum layer 11 are provided on at least one of the surfaces of the resin layers 12 and 13 by, for example, pressing a circular blade. There is no particular limit to the size, shape, arrangement, and number per unit area of ​​the holes, but they should be such that the contact of the aluminum layer 11 with the sodium hydroxide aqueous solution, which will also be described later, is sufficiently promoted in the preheating process and the third process, which will be described later. The holes may penetrate the aluminum layer 11. Also, if the holes are provided from the resin layer 12, they may penetrate the aluminum layer 11 and the resin layer 13, and if the holes are provided from the resin layer 13, they may penetrate the aluminum layer 11 and the resin layer 12. In these cases, the holes are holes that penetrate the composite resin film 1. As described above, there is no particular limit to the size, shape, arrangement, and number per unit area of ​​the holes, but it is possible that providing the holes results in a decrease in the strength of the composite resin film 1. It is necessary to note that the composite resin film 1 needs to have holes so that the composite resin film 1 does not break in the above-mentioned cases.

[0020] The technique for providing the grooves or holes in the composite resin film 1 may be well known or may be based on a known technique. Hereinafter, a method for drilling holes in the composite resin film 1 will be described. As described above, the composite resin film 1 in this embodiment is long and in a roll shape. In this embodiment, the rolled composite resin film 1 is continuously unwound (pulled out) from the leading end, and wound up from the leading end to form a roll again (FIG. 2). The roll 1X on the left side in FIG. 1 is the original roll being unwound, and the roll 1Y on the right side is a new roll that is made by rewinding. In other words, the rolled composite resin film 1 is rewound from the original roll 1X onto a new roll 1Y. Note that, although not limited thereto, in this embodiment, the original roll 1X may or may not have a core in the center of the roll 1X, but the new roll 1Y does not have a core. Such rewinding of the rolled composite resin film 1 can be easily achieved by existing technology. For example, this can be achieved by rotating the original roll X1 of the composite resin film 1 and the new roll 1Y of the composite resin film 1 at an appropriate speed so that an appropriate tension is applied to the portion (hereinafter referred to as the "pulling out portion 1Z") before being unwound from the original roll 1X and wound onto the new roll 1Y. In this embodiment, the rewinding of the composite resin film 1 from the roll 1X to the roll 1Y is performed continuously without stopping, although this is not limited to this. If necessary to change the traveling direction of the composite resin film 1, an auxiliary roller 2 (which may be a so-called free roller that is not driven) can be freely arranged as necessary. In this embodiment, a hole punching device 3 is disposed in the above-mentioned pull-out section 1Z. The hole punching device 3 has a function of punching holes in the composite resin film 1 that continuously passes through the pull-out section 1Z. Such hole punching devices 3 are publicly known or well-known, and therefore, as the hole punching device 3, any appropriate publicly known or well-known device can be used. To briefly explain the principle so that it is easy to understand, the hole punching device 3 comprises a movable member 31 that can move up and down as indicated by the arrow, and a base 32 that supports from below the composite resin film 1 that passes through the hole punching device 3. The movable member 31 is configured to repeatedly move up and down at predetermined time intervals. When the movable member 31 is at its lowest position, it is in contact with the base 32, and when it is at its highest position, it is located above the composite resin film 1. A blade (not shown) is provided on the underside of the movable member 31. When the movable member 31 comes into contact with the base 32, the blade punches a plurality of holes in the composite resin film 1 that is located between the movable member 31 and the base 32.

[0021] An example of holes punched by the hole punching device 3 in the composite resin film 1 is shown in FIG. 3. FIG. 3 is a plan view of the composite resin film 1 that has passed through the hole punching device 3. The vertical direction in FIG. 3 is the length direction of the composite resin film 1. A large number of holes 15 are punched in the composite resin film 1. The holes 15 are circular in this embodiment, although not limited thereto. The holes 15 are punched uniformly throughout the composite resin film 1 in this embodiment, although not limited thereto. The holes 15 in this embodiment penetrate the composite resin film 1. The holes 15 included in the range surrounded by the dashed line α in the figure are punched together when the movable member 31 comes into contact with the base 32 once. In other words, a blade (multiple blades) capable of punching such holes 15 together is provided on the lower surface of the movable member 31. Assuming that the speed of the composite resin film 1 moving within the hole punching device 3 is constant, increasing the time interval at which the movable member 31 is raised and lowered increases the range within the range α where no holes 15 exist, thereby reducing the number of holes 15 per unit area of ​​the composite resin film 1. In this way, by appropriately setting the speed of movement of the composite resin film 1 and the timing of the up and down movement of the movable member 31, it is possible to adjust the number of holes 15 provided per unit area in the composite resin film 1. The composite resin film 1 in which the holes 15 have been punched by the punching device 3 is taken up onto a roll 1Y. An advantage of punching holes 15 in composite resin film 1 when rewinding from roll 1X to roll 1Y is that holes 15 can be punched efficiently and continuously over the entire surface of composite resin film 1. Also, even if composite resin film 1 is tightly wound on roll 1X, it is possible to rewind composite resin film 1 loosely on roll 1Y, which makes it easier for the aqueous sodium hydroxide solution to penetrate between the composite resin film 1 on roll 1Y when performing the third process described below.

[0022] In the above example, the holes 15 made in the composite resin film 1 are holes 15 penetrating the composite resin film 1, but the holes 15 do not need to be through holes as long as they reach the aluminum layer 11 of the composite resin film 1. For example, by using a half-cut technique, it is easy to create a hole that is not a through hole that reaches the aluminum layer 11 from any of the resin layers 12, 13. In addition, in order to create a groove that reaches the aluminum layer 11 from any of the resin layers 12, 13, for example, it is sufficient to simply apply a blade to the flowing composite resin film 1. In this way, a groove extending in the length direction of the composite resin film 1 can be provided on the surface of the composite resin film 1. In this way, the properties of the grooves or holes provided in the composite resin film 1 can be various, but it will be obvious to those skilled in the art that appropriate measures can be taken with the hole-making device 3 in accordance with the properties of the required grooves or holes.

[0023] Thus, the first process is completed. Next, the second process is performed. In the second process, the composite resin film 1 that has been subjected to the first process is submerged in an aqueous sodium hydroxide solution. The sodium hydroxide concentration of the aqueous sodium hydroxide solution is set to 9.72% to 23.9%. Although not limited to this, in this embodiment, an aqueous sodium hydroxide solution with a concentration of 13.0% to 22.0% is used. The aqueous sodium hydroxide solution contains substantially only water and sodium hydroxide, ignoring impurities. In this embodiment, the composite resin film 1 in the form of a roll 1Y is submerged in a sodium hydroxide solution as follows. First, a wire 4 is passed through the center of the roll 1Y. Then, the roll 1Y is lifted up by the wire 4 (FIG. 4(A)). Then, the roll 1Y is lowered and placed in a water tank 6 containing an aqueous sodium hydroxide solution 5 in which the concentration of sodium hydroxide has been adjusted to the above-mentioned concentration. This completes the second step.

[0024] After the second step is completed, a pre-heating step is performed before the third step is performed in this embodiment. The preheating step is carried out before carrying out the third step described below. The preheating process is carried out such that at the start of the preheating process (= the end of the second process), that is, at the time when the roll 1Y (composite resin film 1) is put into the aqueous sodium hydroxide solution 5, the temperature of the aqueous sodium hydroxide solution 5 is set to a temperature lower than 20°C (for example, a temperature higher than 15°C and lower than 20°C), and then the temperature of the aqueous sodium hydroxide solution 5 is raised to a predetermined temperature (a predetermined temperature between 25°C and 50°C) in the third process described below. To make this possible, appropriate measures can be taken, such as providing the water tank 6 storing the sodium hydroxide aqueous solution 5 with a sensor for measuring the temperature of the sodium hydroxide aqueous solution 5 at that time and a heater for raising the temperature of the sodium hydroxide aqueous solution 5 measured by the sensor to a desired temperature. Of course, since techniques for adjusting the temperature of the solution in the water tank 6 to a desired temperature are publicly known or well-known, such publicly known or well-known techniques can be applied to the water tank 6. In addition, in order to make the temperature of the sodium hydroxide aqueous solution 5 in the water tank 6 as uniform as possible regardless of the location, it is preferable to provide the water tank 6 with appropriate means for stirring the sodium hydroxide aqueous solution 5. As the means for stirring, for example, a movable stirring rod that is a rod for stirring the sodium hydroxide aqueous solution 5, a pump for creating a water current in the sodium hydroxide aqueous solution 5, and an aeration device for creating an up-down convection current in the sodium hydroxide aqueous solution 5 can be used. The means for stirring is used to continuously stir the sodium hydroxide aqueous solution 5 after the second process is completed. The preheating process is performed for as short a time as possible within a range from 10 to 30 minutes that does not cause an excessive amount of hydrogen to be generated, preferably for about 10 to 20 minutes. This is because, when the composite resin film 1 is placed in the aqueous sodium hydroxide solution 5 that is at a temperature higher than a certain temperature, for example, higher than 30°C, a chemical reaction specified by the formula (1) described below occurs vigorously, and a large amount of hydrogen may be generated. Therefore, for example, if the temperature of the aqueous sodium hydroxide solution 5 in the third process is relatively low, such as about 25°C, the preheating process does not need to be performed. For example, when the preheating process is performed, the temperature of the aqueous sodium hydroxide solution 5 can be increased by 1° C. to 2° C. per minute.

[0025] After the preheating process is completed, the third process is carried out. The third step is a treatment in which, while maintaining the temperature of the sodium hydroxide aqueous solution 5 at a predetermined temperature between 25°C and 50°C, the composite resin film 1 is continuously submerged in the sodium hydroxide aqueous solution until almost all (98% or more) of the aluminum constituting the aluminum layer 11 is dissolved. During the third step, an aqueous sodium hydroxide solution 5 enters the gaps in the composite resin film 1 constituting the roll 1Y. The aqueous sodium hydroxide solution 5 comes into contact with the aluminum layer 11 exposed from the edge of the composite resin film 1, and also comes into contact with the aluminum layer 11 exposed from the end faces of the numerous holes 15 formed in the composite resin film 1. In the third step, the aqueous sodium hydroxide solution 5 is continuously stirred.

[0026] When the sodium hydroxide aqueous solution 5 comes into contact with the aluminum in the aluminum layer 11, the reactions represented by the following chemical formulas (1) and (2) occur. Al + NaOH + 3 H2O → Na[Al(OH)4] + 3 / 2 H2……(1) Al + 3NaOH → Al(OH)3……(2) All of these reactions dissolve aluminum, but the Al(OH)3 produced in the reaction shown in chemical formula (2) precipitates in an aqueous sodium hydroxide solution 5. In the sodium hydroxide aqueous solution 5, the following reaction represented by chemical formula (3) also occurs. Al(OH)3+ NaOH → Na[Al(OH)4]……(3) In reaction (3), the Al(OH)3 produced in reaction (2) dissolves again in the sodium hydroxide solution 5. As this reaction occurs, the amount of precipitate in the sodium hydroxide solution 5 decreases. As described above, when the third process is being carried out, the sodium hydroxide concentration of the aqueous sodium hydroxide solution 5 is set to 9.72% to 23.9% (preferably 13.0% to 22.0%, and in this embodiment, it is set to be within this range), and the temperature of the aqueous sodium hydroxide solution 5 is maintained at 25°C to 50°C. This prevents the above-mentioned reaction (2) from occurring too slowly and the above-mentioned reaction (3) from occurring too slowly during the third step, thereby preventing a large amount of Al(OH)3 from precipitating in the aqueous sodium hydroxide solution 5. As a result, when the sodium hydroxide concentration of the aqueous sodium hydroxide solution 5 is between 13.0% and 22.0%, the aluminum constituting the aluminum layer 11 in the composite resin film 1 is almost completely dissolved in about 8 hours. Also, the concentration of sodium hydroxide in the sodium hydroxide aqueous solution 5 can be set to 14.1% to 20.5%, and the temperature of the sodium hydroxide aqueous solution 5 in the third step can be kept at 30° C. or higher. In this way, the time required to dissolve almost all of the aluminum in the aluminum layer 11 is almost certainly within six hours. The concentration of sodium hydroxide in the aqueous sodium hydroxide solution 5 can be set to 13.0% to 21.5%, and the temperature of the aqueous sodium hydroxide solution 5 in the third step can be kept at 35° C. or higher. In this way, the time required to dissolve almost all of the aluminum in the aluminum layer 11 is almost certainly within six hours.

[0027] When the third step is carried out, the temperature of the aqueous sodium hydroxide solution 5 is kept between 25° C. and 50° C. However, the temperature of the aqueous sodium hydroxide solution 5 does not need to be constant throughout the execution of the third step, and may be changed within the above-mentioned temperature range. On the other hand, when the temperature of the aqueous sodium hydroxide solution 5 in the third step is kept constant, it is preferable to control the sodium hydroxide concentration and temperature of the aqueous sodium hydroxide solution 5 as follows. By ensuring that the sodium hydroxide concentration C [%] and temperature T [K] of the sodium hydroxide aqueous solution satisfy the following formula, the effect of almost completely dissolving the aluminum that constitutes the aluminum layer 11 in the composite resin film 1 in approximately 8 hours or less can be more reliably achieved. k 290 (C)+[k 313 (C)-k 290 (C)]×(T-290) / 23≧0.00815 min -1 however, k 290 (C)=0.00157+0.00554×Exp[-0.0141×(C-18.4) 2 ] k 313 (C)=(0.302+2.02×Exp[-0.00881×(C-15.2) 2 ])×k 290 (C) Furthermore, if the sodium hydroxide concentration C [%] and temperature T [K] of the sodium hydroxide aqueous solution satisfy the following formula, the effect of almost completely dissolving the aluminum constituting the aluminum layer 11 in the composite resin film 1 in approximately 6 hours or less can be more reliably obtained. k 290 (C)+[k 313 (C)-k 290 (C)]×(T-290) / 23≧0.0100 min -1 however, k 290 (C)=0.00157+0.00554×Exp[-0.0141×(C-18.4) 2 ] k 313 (C)=(0.302+2.02×Exp[-0.00881×(C-15.2) 2 ])×k 290 (C)

[0028] <Test Example> The test was carried out under the following conditions: First, a composite resin film 1 having a cross section shown in Figure 5 was prepared. This composite resin film 1 has an aluminum layer 11 made of aluminum, and resin layers 12 and 13 made of PE. The resin layer 13 is separated into a first outer resin layer 13A and a second outer resin layer 13B. The first outer resin layer 13A is made of PE, and the second outer resin layer 13B is made of PET. The thicknesses of the aluminum layer 11, the resin layer 12, the first outer resin layer 13A, and the second outer resin layer 13B are 9 μm, 30 μm, 13 μm, and 25 μm, respectively. The above-mentioned composite resin film 1 was subjected to a treatment corresponding to the first step of the present application. Specifically, a large number of holes were drilled evenly throughout the composite resin film 1, penetrating the composite resin film 1. The holes were circular, with a diameter of 3.5 mm, and the spacing between the holes in both the vertical and horizontal directions was 8 mm when measured between the centers of the holes. The composite resin film 1 used in the test was a rectangle with a length of 3500 mm and a width of 380 mm. The experiment was performed with such a long composite resin film 1 wound in a roll with the width direction being the width. Nine such rolled composite resin films 1 were prepared and submerged in several aqueous sodium hydroxide solutions with different sodium hydroxide concentrations and temperatures (as will be described later, the temperature may be changed by performing a process equivalent to the preheating process described in this embodiment), and the percentage of the aluminum layer 11 in the composite resin film 1 that had already dissolved was basically observed every three hours (180 minutes).

[0029] The test results are shown in Table 1 in FIG. Nine tests were conducted, numbered Test 1 through Test 9, as indicated by the numbers 1 through 9 in the Test No. column of Table 1. The column "Concentration of sodium hydroxide" indicates the concentration of sodium hydroxide in the aqueous sodium hydroxide solution used in each test. The aqueous sodium hydroxide solution was prepared by dissolving sodium hydroxide in water. The temperature described in the "Temperature" column is the temperature at which the third step in this application is carried out. In all of Tests 1 to 9, the temperature at which the third step is carried out is constant. In Tests 2 to 5 and 9, the temperature of the aqueous sodium hydroxide solution was kept at the temperature indicated in each column continuously after the composite resin film 1 was immersed in the aqueous sodium hydroxide solution. In the present application, this means that the temperature of the aqueous sodium hydroxide solution was kept constant while the second and third steps were being carried out. In Test 1 and Tests 6 to 8, the temperature of the aqueous sodium hydroxide solution was 17°C when the composite resin film 1 was submerged in the aqueous sodium hydroxide solution, and the temperature of the aqueous sodium hydroxide solution was then raised to the temperature indicated on the right side of the arrow (for example, 40°C in the case of Test 1). In terms of the present application, this means that the temperature of the aqueous sodium hydroxide solution when the second process is carried out (i.e., when the composite resin film 1 is inserted) is 17°C, and the temperature of the aqueous sodium hydroxide solution in the third process is the temperature indicated on the right side of the arrow. Also, the time period during which the temperature of the aqueous sodium hydroxide solution rises from 17°C to the temperature indicated on the right side of the arrow is the preheating process referred to in the present application. In this experiment, the temperature of the aqueous sodium hydroxide solution was raised by 1°C per minute. Therefore, the time required to raise the temperature from 17°C to the temperature indicated on the right side of the arrow in each test is the difference (in minutes) between the numbers on both sides of the arrow. In addition, the "aluminum dissolution rate after the start of the test" indicates the aluminum dissolution rate after 180 minutes (3 hours), 360 minutes (6 hours), 540 minutes (9 hours), 720 minutes (12 hours), 900 minutes (15 hours), and 1800 minutes (30 hours), when the test start time is the time when the composite resin film 1 is put into the sodium hydroxide aqueous solution. Observations were made visually. In addition, in the same column, an "x" mark means that "observation was discontinued." In Test 2, Test 3, and Test 6, the dissolution rate reached 100% (i.e., 100% of the aluminum was dissolved) and further observation was no longer necessary, so observation was discontinued. In Test 9, an extremely large amount of hydrogen was generated immediately after the composite resin film 1 was placed in the sodium hydroxide aqueous solution, so the test itself was discontinued after about 1 minute. However, according to observation for about 1 minute before the test was discontinued, it seemed that almost all of the aluminum would dissolve within 6 hours. In addition, a "-" in the same column means that "the experiment was not stopped, but the aluminum dissolution rate was not observed at that time."

[0030] <Considerations on test results> The overall trends revealed are as follows: First, we focus on tests 2 to 5. In tests 2 to 5, the temperature of the sodium hydroxide aqueous solution was 17°C from the time composite resin film 1 was placed in the sodium hydroxide aqueous solution throughout the test, but the sodium hydroxide concentration of the sodium hydroxide aqueous solution varied from 10% to 40% in each test. The reaction rate was faster in Test 3, where the sodium hydroxide concentration of the aqueous sodium hydroxide solution was 20%, than in Test 2, where the sodium hydroxide concentration of the aqueous sodium hydroxide solution was 10%, and the aluminum dissolution rate reached 100% in a short time. However, the reaction rate slowed in Test Example 4, where the concentration was 30%, and the reaction rate slowed further in Test Example 5, where the concentration was 40%, so that the aluminum dissolution rate did not reach 100% even after 1800 minutes had passed. This shows that the higher the concentration of sodium hydroxide in the aqueous sodium hydroxide solution, the faster the reaction rate at which aluminum dissolves. Next, we look at trials 1 and 6 to 8. Test 1 and tests 6 to 8 have in common that they begin with a preheating process at 17°C and then the temperature of the aqueous sodium hydroxide solution is maintained at 40°C. However, the sodium hydroxide concentration of the aqueous sodium hydroxide solution differs in each test, ranging from 5% to 40%. In Test 1, where the sodium hydroxide concentration of the aqueous sodium hydroxide solution is 5%, even if the temperature of the aqueous sodium hydroxide solution is raised from 17°C to 40°C, the reaction rate is slow, and the aluminum dissolution rate does not reach 100% even after 1800 minutes have passed. In contrast, in Test 6, where the sodium hydroxide concentration of the aqueous sodium hydroxide solution is 20%, the aluminum dissolution rate reaches 100% in an extremely short time (360 minutes). In Test 7, where the concentration is 30%, the reaction rate is slower than in Test 6, and in Test 8, where the concentration is 40%, the reaction rate is even slower, and the aluminum dissolution rate does not reach 100% even after 1800 minutes. These show that the higher the concentration of sodium hydroxide in the aqueous sodium hydroxide solution, the faster the reaction rate of aluminum dissolution does not necessarily become. In addition, when comparing Tests 3 to 5, in which the temperature of the aqueous sodium hydroxide solution in the second step in the present application is 17°C, with Tests 6 to 8, in which the temperature of the aqueous sodium hydroxide solution in the second step in the present application is 40°C, the latter, in which the temperature of the aqueous sodium hydroxide solution is higher, has a faster reaction rate than Test 3. However, when comparing Tests 4 and 7, and Test 5 and Test 8, with the exception that Test 8 has a faster reaction rate than Test 5 until halfway through, the latter, in which the temperature of the aqueous sodium hydroxide solution is higher, ultimately has a slower reaction rate. These indicate that the higher the temperature of the sodium hydroxide in the aqueous sodium hydroxide solution, the faster the reaction rate of aluminum dissolution does not necessarily become. Finally, test 9. As already mentioned, it was practically impossible to carry out Test 9. Test 9 and Test 6, which had the fastest reaction rate among the tests, were consistent in terms of the sodium hydroxide concentration in the sodium hydroxide aqueous solution, and the temperature of the sodium hydroxide aqueous solution in the third process was also consistent at 40°C. However, in Test 9, in which the composite resin film 1 was placed in the sodium hydroxide aqueous solution at 40°C, too much hydrogen was generated, making it impossible to continue the test for a long period of time.

[0031] As described above, it has been found that simply increasing the concentration of sodium hydroxide in the aqueous sodium hydroxide solution or simply increasing the temperature of the aqueous sodium hydroxide solution does not necessarily increase the reaction rate of the reaction related to the dissolution or decomposition of aluminum. Based on this, we decided to use a general formula to determine the reaction rate when composite resin film 1 is immersed in an aqueous sodium hydroxide solution, using the concentration C [%] of sodium hydroxide in the aqueous sodium hydroxide solution and the temperature T [K] of the aqueous sodium hydroxide solution as variables. From the calculated reaction rates, we then determined the relationship between the concentration C [%] and temperature T [K] at which the time required for almost all of the aluminum (98%) to dissolve is 8 hours or less, and the relationship between the concentration C [%] and temperature T [K] at which the time required for almost all of the aluminum to dissolve is 6 hours or less.

[0032] The reactions that occur when aluminum dissolves in an aqueous solution of sodium hydroxide are shown in the above chemical equations (1) and (2). To make it easier to analyze these chemical reactions, we assume that these are first-order reactions (i.e., the reduction of aluminum follows a first-order reaction rate equation). Under this assumption, the following definitions are made: Weight of aluminum at the start of the test: Ao [kg] Weight of aluminum after t [min] from the start of the test: A(t) [kg] Reaction rate constant: k1 [min -1 ] Assuming that the aluminum dissolution reaction follows a first-order reaction rate equation, the following (Equation 1) holds true. -d[A] / dt = k1[A] ……(Formula 1) From (Equation 1), the following (Equation 2) is obtained. ln [A(t) / Ao] = -k1t ……(Formula 2) (Equation 2) means that after t minutes have passed since the start of the test, aluminum has decreased, the amount of aluminum decreases as time passes, and the larger the reaction rate constant k1, the greater the amount of aluminum that decreases. Generally, when the concentration of the sodium hydroxide solution is high or the reaction temperature is high, the reaction rate constant is large and the rate at which aluminum dissolves increases.

[0033] Next, the reaction rate of the aluminum dissolving reaction is calculated from (Equation 2) and the test result data. When the concentration of the sodium hydroxide aqueous solution was 20% and the reaction temperature was 17° C., that is, in Test 3, the amount of aluminum changed as shown in Table 2 in FIG. Next, by plotting the natural logarithm of the reaction rate (natural logarithm ln [A(t) / Ao]) when the concentration of the sodium hydroxide solution is 20% and the reaction temperature is 17°C against the reaction time t using equation 2, ln(A(t) / Ao) = - k1t, we obtained the straight line for "17°C, 20%" in Graph 1 shown in Figure 8. Similarly, the natural logarithm of the reaction rate (natural logarithm ln [A(t) / Ao]) was calculated when the concentration of the sodium hydroxide aqueous solution was 10% and the reaction temperature was 17°C (Test 2). When this was plotted against the reaction time t, a straight line for "17°C, 10%" was obtained as shown in Graph 1. Furthermore, when the concentrations of the sodium hydroxide aqueous solution were 30% and 40% and the reaction temperature was 17°C (Tests 4 and 5), the natural logarithm of the reaction rate (natural logarithm ln [A(t) / Ao]) was calculated and plotted against the reaction time t, the straight lines "17°C, 30%" and "17°C, 40%" in Graph 1 were obtained. The plotted points were approximated by a Gaussian distribution curve (k=P0+P1×Exp[-((C-P2) / P3)2] (k is the reaction rate constant, C is the concentration)) using the well-known least squares method, and the parameters P0, P1, P2, and P3 with the smallest approximation error were obtained. This completes the task of plotting the natural logarithm of the reaction rate (natural logarithm ln [A(t) / Ao]) against reaction time t for all tests from Test 2 to Test 5, which are the groups in which the reaction temperature of the sodium hydroxide aqueous solution was 17°C.

[0034] Next, for the group where the reaction temperature of the sodium hydroxide aqueous solution was 40°C, i.e., Test 1 and Test 6 to Test 8, we similarly plotted the natural logarithm of the reaction rate (natural logarithm ln [A(t) / Ao]) against reaction time t. However, in Test 1 and Tests 6 to 8, to be precise, the reaction temperature was not continuously 40°C. A preheating process was carried out in which the temperature of the aqueous sodium hydroxide solution, which was 17°C at the start of the tests, was raised to 40°C over a period of 23 minutes. However, considering that the execution time of the preheating process is affected by the maximum temperature reached, the reaction temperature was set to a representative temperature condition of 40°C, the natural logarithm of the reaction rate (natural logarithm ln [A(t) / Ao]) was calculated, and the natural logarithm of the reaction rate (natural logarithm ln [A(t) / Ao]) was plotted against the reaction time t. As a result, graph 2 shown in FIG. 9 was obtained. In Graph 2, the line for Test 1 is annotated "40°C, 5%," the line for Test 6 is annotated "40°C, 20%," and the line for Test 7 is annotated "40°C, 30%." Also, two straight lines were created from Test 8. In Test 8, aluminum dissolution proceeds rapidly from the start of the test until 180 minutes, but after 180 minutes, aluminum dissolution has almost stopped. In other words, Test 8 shows a state in which aluminum dissolution proceeds and a state in which aluminum dissolution is strongly inhibited by precipitated Al(OH)3. Therefore, two straight lines were created from Test 8: one for the former and one for the latter. The solid line annotated "40°C, 40% A" is the former straight line, and the dashed line annotated "40°C, 40% B" is the latter straight line. Graphs 1 and 2 are summarized below. In both Group 1 shown in Graph 1 with a reaction temperature of 17°C and Group 2 shown in Graph 2 with a reaction temperature of 40°C, the weight of aluminum decreases over reaction time and the logarithmic value becomes smaller. In the case of graph 1, the rate of decrease is greater when the concentration of the aqueous solution is 20% than when it is 10%. However, when the concentration reaches 30%, the sodium aluminates (a typical example is Al(OH)3) that are produced precipitate as solids, making it difficult for the aqueous sodium hydroxide solution to come into contact with aluminum, slowing down the reaction rate. An even more significant decrease in the reaction rate was observed when the concentration of the aqueous sodium hydroxide solution was 40%. In the case of graph 2, the rate of decrease is greater when the concentration of the aqueous solution is 20% than when it is 5%. However, it was found that when the concentration reaches 30%, the fluidity of the sodium hydroxide aqueous solution deteriorates, making contact with the aluminum difficult, and the reaction rate slows down. When the concentration of the sodium hydroxide aqueous solution is 40%, the aluminum dissolves quickly at the beginning of the reaction, but due to poor fluidity, contact with the sodium hydroxide slows down, and a significant drop in the reaction rate was observed halfway through.

[0035] Let us refer again to Equation 2 above. ln [A(t) / Ao] = -k1t ……(Formula 2) As is clear from this formula, the reaction rate constant (k1) is the slope of each line shown in Graph 1 and Graph 2. The reaction rate constants in each test, which are the slopes of the multiple lines shown in Graph 1 and Graph 2, are listed in Table 3 in Figure 10, linked to the reaction temperatures in each test for each concentration of sodium hydroxide in the sodium hydroxide aqueous solution. In Table 3, the numbers in the columns for sodium hydroxide concentrations of 10%, 20%, 30%, and 40% at 17°C (290K) are the slopes (or more accurately, multiplied by -1) of the lines marked "17°C, 10%", "17°C, 20%, "17°C, 30%, and 17°C, 40%" in Graph 1. Note that the underlined value in Table 3 for a sodium hydroxide concentration of 5% at 17°C (290K) is an estimate obtained by halving the slope value for "17°C, 10%" based on the assumption that if the concentration is half, the reaction rate will be roughly half if the concentration is half, in a concentration range where fluidity is not an issue. In Table 3, the numbers in the columns for sodium hydroxide concentrations of 5%, 20%, 30%, and 40% at 40°C (313K) are the slopes (or more accurately, multiplied by -1) of the lines marked "40°C, 5%", "40°C, 20%, "40°C, 30%, and "40°C, 40%B" in Graph 2. Note that the underlined value in Table 3 for a sodium hydroxide concentration of 10% at 40°C (313K) is an estimated value determined by averaging the slope values ​​for "40°C, 5%" and "40°C, 20%", because there is no actual measured data. In this manner, the reaction rate constants when the temperature of the aqueous sodium hydroxide solution was 17°C and 40°C were determined for various concentrations of the aqueous sodium hydroxide solution.

[0036] Next, the concentration C (%) of sodium hydroxide in the sodium hydroxide solution is plotted on the horizontal axis, and the reaction rate constant k (10 3 / min) was taken and plotted for the cases where the temperature of the aqueous sodium hydroxide solution was 17°C and 40°C. Then, a curve fit was performed to connect the five points where the temperature of the sodium hydroxide aqueous solution was 17° C. with a Gaussian distribution curve. As a result, Graph 3 shown in FIG. 11 was obtained. The graph marked 17°C is a curve showing the relationship between the concentration C (%) of sodium hydroxide in the aqueous sodium hydroxide solution when the temperature of the aqueous sodium hydroxide solution is 17°C and the reaction rate constant. The graph marked 40°C is a curve showing the relationship between the concentration C (%) of sodium hydroxide in the sodium hydroxide solution when the temperature of the sodium hydroxide solution is 40°C and the reaction rate constant.

[0037] Next, the reaction rate constant k when the temperature of the sodium hydroxide solution is 17°C, i.e., 290K, is calculated as follows, assuming that the concentration C (%) of sodium hydroxide in the sodium hydroxide solution is a variable: 290 (C) was sought. Reaction rate constant k 290 The curve showing the concentration dependence of (C) was approximated by the following Gaussian function (Equation 3). k 290 (C) = P0 + P1×Exp[-((C - P2) / P3) 2 ]…… (Formula 3) Here, C is the concentration of the aqueous sodium hydroxide solution of 5 to 40 wt %. The parameters P0 to P3 in Equation 3 calculated from the graph marked 17°C in Graph 3 were P0 = 0.00157, P1 = 0.00554, P2 = 18.4, P3 = 8.41. Substituting these parameters into Equation 3 and rearranging it, k 290 (C) is expressed as the following (Equation 4). k 290 = 0.00157+0.00554×Exp[-0.0141×(C-18.4) 2 ]……(Formula 4) In addition, to estimate the reaction rate under other temperature conditions that have not been tested, the reaction rate constant (k 290 (C)) and the reaction rate constant (k 313 (C)) 313 The equation for the approximation curve of (C)) (Equation 5) was obtained. Ratio 313 (C) = K 313 (C) / K 290 (C) = (0.302+2.02×Exp[-0.00881×(C-15.2) 2 ])……(Formula 5) By rearranging this (Equation 5), the reaction rate constant (k 313 (C)) is expressed as follows (Equation 6). K 313 (C)=(0.302+2.02×Exp[-0.00881×(C-15.2) 2 ])×K 290 (C) ...(Formula 6)

[0038] Next, the reaction rate constant k of the sodium hydroxide solution at a temperature of 17°C (290 K) obtained as described above 290 (C) and the reaction rate constant k at 40°C (313 K) 313 Using these two equations, we obtained the following equation (7) for calculating the reaction rate constant k(C,T) for the aluminum dissolution reaction at any reaction temperature T(k) and any sodium hydroxide concentration C(%). k(C,T) = k 290 (C)+[k 313 (C)-k 290 (C)]×(T-290) / 23……(Formula 7) where k 290 (C) and k 313 (C) is as follows, as shown in (Equation 4) and (Equation 6). k 290 (C)=0.00157+0.00554×Exp[-0.0141×(C-18.4) 2 ] k 313 (C)=(0.302+2.02×Exp[-0.00881×(C-15.2) 2 ])×k 290 (C) This allowed us to obtain a general equation for the reaction rate constant k(C,T) for any reaction temperature T(k) and any sodium hydroxide concentration C(%).

[0039] Using the above-mentioned general formula (Equation 7), the relationship between the concentration C (%) of sodium hydroxide in the aqueous sodium hydroxide solution and the reaction rate constant (the curve showing the relationship between the two will be referred to as the "reaction curve" hereinafter) is shown in Graph 4 in FIG. 12 when the temperatures of the aqueous sodium hydroxide solution are 17°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, and 50°C.

[0040] On the other hand, the reaction rate constants were determined for the cases where the time from when the composite resin film 1 was placed in the sodium hydroxide aqueous solution until almost all of the aluminum in the aluminum layer 11 was dissolved, i.e., 98%, was 8 hours and when it was 6 hours. If the time was 8 hours, a worker could carry out the aluminum removal method in, for example, 8 hours out of a 10-hour workday, and if the time was 8 hours, a worker could carry out the aluminum removal method in, for example, 6 hours out of an 8-hour workday, making the aluminum removal method practical. The reaction rate constant when the time from when the composite resin film 1 is put into the sodium hydroxide aqueous solution until 98% of the aluminum in the aluminum layer 11 is dissolved is 8 hours can be calculated based on (Formula 2). (Formula 2) is as follows. ln [A(t) / Ao] = -k1t ……(Formula 2) The above-mentioned conditions are substituted into this. ln[(100-98) / 100] = - k ×8×60 -3.91 = -k x 8 x 60 k = 0.00815 min -1 Similarly, the reaction rate constant when it takes 6 hours from when the composite resin film 1 is put into the aqueous sodium hydroxide solution until 98% of the aluminum in the aluminum layer 11 is dissolved can be calculated as follows. ln[(100-98) / 100] = - k ×6×60 -3.91 = -k x 6 x 60 k = 0.0100 min -1 These two values ​​are written into graph 4 shown in FIG. 12 with the symbols 8h and 6h.

[0041] Graph 4 reveals the following: The reaction curves do not lie above the line 8h when the reaction temperature, i.e., the temperature of the aqueous sodium hydroxide solution in the second process, is 17° C. and 20° C. This indicates that when the reaction temperature is 17° C. and 20° C. (or an intermediate temperature), no matter what the concentration of sodium hydroxide in the aqueous sodium hydroxide solution is, the time from when the composite resin film 1 is put into the aqueous sodium hydroxide solution until 98% of the aluminum in the aluminum layer 11 is dissolved will never be within a practical time range of less than 8 hours.

[0042] On the other hand, all of the reaction curves with reaction temperatures from 25°C to 50°C have a portion located above the line 8h. Therefore, according to these reaction curves, if the concentration of sodium hydroxide in the sodium hydroxide aqueous solution is within a certain range among the reaction curves from 25°C to 50°C, it can be seen that there are cases in which the time from when the composite resin film 1 is put into the sodium hydroxide aqueous solution until 98% of the aluminum in the aluminum layer 11 is dissolved is a practical time range of less than 8 hours. Here, when the reaction curve at 50°C intersects with the line 8h, the concentration of sodium hydroxide in the sodium hydroxide aqueous solution on the low concentration side is 9.72%, and the concentration on the high concentration side is 23.9%. Therefore, it can be seen that the time from when the composite resin film 1 is put into the sodium hydroxide aqueous solution until 98% of the aluminum in the aluminum layer 11 is dissolved can be made to be less than 8 hours by setting the concentration of sodium hydroxide in the sodium hydroxide aqueous solution to 9.72% to 23.9% and setting the temperature of the sodium hydroxide aqueous solution in the third process to 25°C to 50°C (not necessarily constant). As described above, all of the reaction curves with reaction temperatures from 25°C to 50°C have a portion located above the line 8h. When the reaction curve for 25°C intersects with the line 8h, the concentration of sodium hydroxide in the aqueous sodium hydroxide solution on the low concentration side is 13.0%, and the concentration on the high concentration side is 22.0%. Within that concentration range, the entire length of all reaction curves at 25°C or higher will be located above 8h. Therefore, by setting the concentration of sodium hydroxide in the aqueous sodium hydroxide solution to 13.0% to 22.0% and setting the temperature of the aqueous sodium hydroxide solution in the third process to 25°C to 50°C (not necessarily constant), it is possible to reduce the time from when the composite resin film 1 is put into the aqueous sodium hydroxide solution until 98% of the aluminum in the aluminum layer 11 is dissolved to less than 8 hours.

[0043] Furthermore, all of the reaction curves with reaction temperatures from 30°C to 50°C have a portion located above the line 6h. When the reaction curve for 30°C intersects with the line 6h, the concentration of sodium hydroxide in the aqueous sodium hydroxide solution on the low concentration side is 14.1%, and the concentration on the high concentration side is 20.5%. Within that concentration range, the entire length of all reaction curves at 30°C or higher will be located above 6h. Therefore, it can be seen that by setting the concentration of sodium hydroxide in the aqueous sodium hydroxide solution to 14.1% to 20.5% and setting the temperature of the aqueous sodium hydroxide solution in the third process to 30°C to 50°C (not necessarily constant), the time from when the composite resin film 1 is put into the aqueous sodium hydroxide solution until 98% of the aluminum in the aluminum layer 11 is dissolved can be reduced to less than 6 hours. In addition, all of the reaction curves with reaction temperatures from 35°C to 50°C have a portion located above the line 6h. When the reaction curve for 35°C intersects with the line 6h, the concentration of sodium hydroxide in the aqueous sodium hydroxide solution on the low concentration side is 13.0%, and the concentration on the high concentration side is 21.5%. Within that concentration range, the entire length of all reaction curves at 35°C or higher will be located above 6h. Therefore, it can be seen that by setting the concentration of sodium hydroxide in the aqueous sodium hydroxide solution to 13.0% to 21.5% and setting the temperature of the aqueous sodium hydroxide solution in the third process to 35°C to 50°C (not necessarily constant), the time from when the composite resin film 1 is put into the aqueous sodium hydroxide solution until 98% of the aluminum in the aluminum layer 11 is dissolved can be reduced to less than 6 hours.

[0044] As described above, the reaction rate constant k(C,T) for the aluminum dissolution rate at any reaction temperature T(k) and any sodium hydroxide concentration C(%) can be expressed by (Equation 7). Assuming that the reaction temperature is constant, if k(C, T) is 0.00815 or more, the time from when the composite resin film 1 is placed in the sodium hydroxide aqueous solution until 98% of the aluminum in the aluminum layer 11 dissolves will be 8 hours or less, and if k(C, T) is 0.0100 or more, the time from when the composite resin film 1 is placed in the sodium hydroxide aqueous solution until 98% of the aluminum in the aluminum layer 11 dissolves will be 8 hours or less. In other words, the concentration C (%) and the constant temperature T (K) are k(C,T) ≧0.00815 min -1 k 290 (C)+[k 313 (C)-k 290 (C)]×(T-290) / 23≧0.00815 min -1 however, k 290 (C)=0.00157+0.00554×Exp[-0.0141×(C-18.4) 2 ] k313 (C)=(0.302+2.02×Exp[-0.00881×(C-15.2) 2 ])×k 290 (C) If this condition is satisfied, the time required from when the composite resin film 1 is put into the sodium hydroxide aqueous solution until 98% of the aluminum in the aluminum layer 11 is dissolved will be 8 hours or less. Also, the concentration C (%) and the constant temperature T (K) are k(C,T) ≧0.0100 min -1 k 290 (C)+[k 313 (C)-k 290 (C)]×(T-290) / 23≧0.0100 min -1 however, k 290 (C)=0.00157+0.00554×Exp[-0.0141×(C-18.4) 2 ] k 313 (C)=(0.302+2.02×Exp[-0.00881×(C-15.2) 2 ])×k 290 (C) If this condition is satisfied, the time from when the composite resin film 1 is put into the sodium hydroxide aqueous solution until 98% of the aluminum in the aluminum layer 11 is dissolved will be 6 hours or less. [Explanation of symbols]

[0045] 1 Composite resin film 5. Sodium hydroxide solution 6. Aquarium 11 Aluminum layer 12 Resin layer 13 Resin layer

Claims

1. 1. A method for removing aluminum from a composite resin film comprising an aluminum layer made of aluminum and two resin layers covering both sides of the aluminum layer, comprising: A first step of providing a groove or a hole extending from a surface of at least one of the two resin layers to the aluminum layer; A second step of immersing the composite resin film having undergone the first step in an aqueous solution of sodium hydroxide having a concentration of 9.72% to 23.9%; a third step of, after the second step, continuously immersing the composite resin film in the sodium hydroxide aqueous solution while maintaining the temperature of the sodium hydroxide aqueous solution at a predetermined temperature of 25° C. to 50° C. until the aluminum constituting the aluminum layer is substantially completely dissolved; a fourth step of removing the composite resin film from which the aluminum layer has been removed after the third step is completed, from the sodium hydroxide aqueous solution; 1. A method for removing aluminum from a composite resin film, comprising:

2. The composite resin film before the first step is performed is long and in a roll shape, In the first step, while the rolled composite resin film is being re-rolled by continuously unwinding the front end and winding the front end, a process is carried out on the composite resin film running between two rolls to provide grooves or holes extending from the surface of at least one of the two resin layers of the composite resin film to the aluminum layer. A method for removing aluminum from the composite resin film according to claim 1.

3. In the first step, a large number of holes are formed in the composite resin film through the composite resin film; A method for removing aluminum from the composite resin film according to claim 1 or 2.

4. In the second step and the third step, a 13.0% to 22.0% aqueous sodium hydroxide solution is used. A method for removing aluminum from the composite resin film according to claim 1.

5. In the second and third steps, a 14.1% to 20.5% aqueous sodium hydroxide solution is used, The predetermined temperature in the third step is 30° C. or higher. A method for removing aluminum from the composite resin film according to claim 1.

6. In the second and third steps, a 13.0% to 21.5% aqueous sodium hydroxide solution is used, The predetermined temperature in the third step is 35° C. or higher. A method for removing aluminum from the composite resin film according to claim 1.

7. In the third step, the predetermined temperature of the sodium hydroxide aqueous solution is constant, and the sodium hydroxide concentration C [%] and the temperature T [K] of the sodium hydroxide aqueous solution satisfy the following formula: A method for removing aluminum from the composite resin film according to claim 1. k 290 (C)+[k 313 (C)-k 290 (C)]×(T-290) / 23≧0.00815 min -1 however, k 290 (C)=0.00157+0.00554×Exp[-0.0141×(C-18.4) 2 ] k 313 (C)=(0.302+2.02×Exp[-0.00881×(C-15.2) 2 ])×k 290 (C)

8. In the third step, the predetermined temperature of the sodium hydroxide aqueous solution is constant, and the sodium hydroxide concentration C [%] and the temperature T [K] of the sodium hydroxide aqueous solution satisfy the following formula: A method for removing aluminum from the composite resin film according to claim 1. k 290 (C)+[k 313 (C)-k 290 (C)]×(T-290) / 23≧0.0100 min -1 however, k 290 (C)=0.00157+0.00554×Exp[-0.0141×(C-18.4) 2 ] k 313 (C)=(0.302+2.02×Exp[-0.00881×(C-15.2) 2 ])×k 290 (C)

9. The temperature of the aqueous sodium hydroxide solution at the time of carrying out the second step is lower than 20° C., After performing the second step, and before performing the third step, A preheating step is carried out to raise the temperature of the aqueous sodium hydroxide solution from a temperature lower than 20° C. to the predetermined temperature in the third step. A method for removing aluminum from the composite resin film according to claim 1.

10. The preheating process is performed for 10 to 30 minutes. A method for removing aluminum from the composite resin film according to claim 9.

Citation Information

Patent Citations

  • JP1975014488A

  • Recycling methods for layered waste film

    JP4574543B2

  • Separation and recovery method for laminated film

    JP6777263B2